Η Αγιότητα στην υπηρεσία της πολιτικής. Οι προπαγανδιστικές συνδηλώσεις της παράστασης του "Βουλγαροκτόνου" Αγίου Δημητρίου - Οικονόμου, Στυλιανός Δημητρίου (Byzantina Symmeikta, 2023)
St. Demetrius, the patron saint of Thessaloniki through the ages, the myroblytos and miracle-worker, is the subject of an extremely rich iconography. In one scene the martyr is depicted on horseback, spearing or unhorsing Ioannitzes, a prominent Bulgarian king (1197-1207). The specific iconographical type was conceived during the 13th century in the frame of the byzantine counter-narrative against the second Bulgarian state’s founding ideology, in order to present the aforementioned ruler’s sudden death as one of Demetrius’ numerous miracles. The diffusion of this scene served multiple objectives of Michael VIII Palaiologos’ propaganda, given that St. Demetrius was considered as one of his personal patron saints, a policy which was followed and expanded by his son and successor, Andronicus II Palaiologos. This paper’s aims are to interpret the propaganda meaning of the representation of St. Demetrius as ‘Bulgar-Slayer’ and to offer suggestions upon its dating, based on sources, coins, lead seals and wall paintings.